Diagnosis and management of duodenal perforations: a narrative review. (3rd August 2019) - Ansari, Daniel; Torén, William; Lindberg, Sarah; Pyrhönen, Helmi-Sisko; Andersson, Roland
Abstract: Duodenal perforation is a rare, but potentially life-threatening injury. Multiple etiologies are associated with duodenal perforations such as peptic ulcer disease, iatrogenic causes and trauma. Computed tomography with intravenous and oral contrast is the most valuable imaging technique to identify duodenal perforation. In some cases, surgical exploration may be necessary for diagnosis. Specific treatment depends upon the nature of the disease process that caused the perforation, the timing, location and extent of the injury and the clinical condition of the patient. Conservative management seems to be feasible in stable patients with sealed perforations. Immediate surgery is required for patients presenting with peritonitis and/or intra-abdominal sepsis. Minimally invasive techniques are safe and effective alternatives to conventional open surgery in selected patients with duodenal perforations. Here we review the current literature on duodenal perforations and discuss the outcomes of different treatment strategies.